Enhancing Research Self-Efficacy among Nursing Students: Findings from A Short Educational Intervention - Juanita Juanita (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: Research self-efficacy is the degree to which students believe they are capable of learning or accomplishing an undergraduate thesis within a specific area of research. The undergraduates who had a high sense of self-efficacy, can complete academic writing on time.Method: This study designed was a quasy quasi-experimental study used a one-group pre-test and post-test design to examine the effect of a educational program on research self-efficacy among nursing students who are completing the undergradute thesis. The ninety students who were eligible was envolved in this program. The study consists of 2 stages, including stage 1: forming an intervention group and assessing the level of student self-efficacy, and  stage 2 consist of 5 sessions. Research Self-Efficacy Scale (RSS) was used to examine the students self efficacy before and after the program, this scale consist of 18 items with 5 point likert scale. Wilcoxon signed rank was used to analyze the effectiveness of the program.Results: This study found that the experimental group had significantly higher research self-efficacy group after participating in this program (Z = -5.821;  p< .05), and the mean research self-efficacy score after the intervension was higher (M = 71.03; SD = 7.48) than before the intervension (M = 66.17; SD = 6.99).Conclusion: the educational program in the current study significantly enhanced research self-efficacy among nursing students. Therefore, it was needed to conduct this program in another school in order to enhance the research self-efficacy among students.